EVIDENCE OF THE PARTICLE CONCENTRATION EFFECT FOR LEAD AND OTHER METALS IN FRESH WATERS BASED ON ULTRACLEAN TECHNIQUE ANALYSES - Benoit G. (My University, 1995)
Ultraclean methods were used to produce reliable concentration data for the trace metals Pb, Ag, and Cd in fresh waters and for Pb, Ag, Cu, and Zn in estuarine waters. Partitioning of metals between filter-retained and filtrate fractions exhibited a dependence on total suspended solids (TSS) concentration. This phenomenon, the particle concentration effect (PCE), has been previously documented almost exclusively in marine and estuarine systems and lab simulations, and mainly for radionuclides. The partition coefficient, Kd, was independent of major ion chemistry and pH, supporting the hypothesis that the PCE is caused by metals associated with colloidal particles but counted with the filtrate (''dissolved'') fraction. Partition coefficients of the measured metals in fresh waters are predictable across the full range of TSS measured, spanning more than two orders of magnitude. The inferred true partition coefficient for Pb (between solution and particles of all size classes) is greater than 107.4, suggesting that truly dissolved Pb concentrations are extraordinarily low. Previously published data are reinterpreted to show that naturally occurring 210Pb also exhibits the PCE. Freshly precipitated Fe oxyhydroxides partition metals exactly like organic detritus and clays in spite of the great difference in their surface chemistry. The same data rule out the possibility that the PCE could be caused by a decrease in surface area (and surface complexation sites) due to resuspension of larger particles under high TSS conditions. A surprising result is that, while the slope of a log (Kd) - log (TSS) plot for 210Pb is the same as for stable lead, absoluteKd values for 210Pb are uniformly lower by a factor of 4. This suggests that 210Pb and stable lead behave differently from each other in the surface waters studied. One possible explanation is that this dissimilarity may be attributable to differences in speciation that are persistent on a time scale of months, corresponding to the water residence time or Pb removal rate.